Sustainable fishing: a study on barrier traps in Indonesia - . Ahmadi; . Iriansyah; Cahyani Lestiani (Marine and Fishery Sciences)
Fishermen from Indonesia are uncertain whether the timing and placement of Belats (guiding barrier traps) affects their catch. To answer this question and improve the long-term viability and productivity of the Belat fishery, this study described the catch composition, productivity, and efficiency of Belat in Tanjung Batu Village, Kotabaru Regency, Indonesia. Two Belats consisting of a leader net, playground, and chamber net, were used in this study: Belat-A was larger than Belat-B in both length and breadth. Belat-A was deployed at 2 km from the shoreline, while Belat-B was installed at 1.5 km away, starting at 10 a.m. over a 24-h and a 48-h period, respectively. Results showed that Belat-A outperformed Belat-B, capturing twice the number of catch (970 versus 460) and 1.6 times the weight (92.6 kg versus 59.1 kg) across ten fish species between 14-50 cm of total length. However, Belat-B achieved similar productivity rates in half the operational time, making it more time-efficient. All fish caught were fresh and marketable, while the method itself was considered environmentally friendly. Several factors that affected the Belat catch and recommendation for upcoming Belat studies are also discussed.